The effects of new topical treatments on management of glaucoma in Scotland: an examination of ophthalmological health care. Issue 5 (1st May 2002) - Bateman, D N; Clark, R; Azuara-Blanco, A; Bain, M; Forrest, J
Abstract : Background: The management of glaucoma has been changed in the past decade by the introduction of new drugs. The impact of these changes on clinical care of patients was examined by examining operation and prescribing rates for glaucoma in four geographical areas of Scotland for the years 1994 to 1999. Methods: A retrospective analysis of national health statistics: primary care prescribing data, hospital derived operation rates, consultant numbers, optometrist numbers, and eye test data, expressed by estimated population at risk of glaucoma. The outcome measures were prescribing volume and cost for glaucoma medications, and operation rates, corrected for population estimated to be at risk of glaucoma (PEG), for trabeculectomy, for Scotland as a whole, and for four geographical "regions" (north east, south east, central, and south west Scotland). Results: Prescribed items per 1000 population estimated to have glaucoma (PEG) increased by 24.9% between 1994 and 1999. This was above the general increase in prescribing in Scotland (17.8%). This increase varied in the four health regions evaluated (14.3% to 31.9%). Prescribing of topical β blockers increased little (6.4%), but there was a large increase in the use of new products (topical prostaglandins, carbonic anhydrase inhibitors, and α2 agonists), at the expense of miotics (47.7% fall), and older sympathomimetics. This change in prescribing pattern was accompanied by a 61.5% increase in cost (range 42.2% to 73.4% in the four regions). New drugs accounted for more than half of total glaucoma expenditure in 1999. Operation rates (corrected for PEG) fell by 45.9% (range 43.1 to 58.6%) between 1994 and 1999. Other indicators suggested increased activity in ophthalmic areas (for example, cataract operations, eye tests, numbers of optometrists and ophthalmic surgeons all increased). Within north east Scotland operation rates decreased and prescribing increased less than in other regions, both from lowest regional baseline in 1994. Conclusions: The introduction of new drug classes has had dramatic effects on the prescribing of glaucoma treatments. There has been a decline in older treatments and an increase in new agents, which has been associated with a large reduction in operation rates for glaucoma in Scotland over 6 years. Comparison of prescribing and operation data indicates regional differences in healthcare delivery for glaucoma.